The Urgency of Fatwa as a Legal Ijtihad on Medical Cannabis Legalization in Indonesia - Rizka, Rizka; Junaidi, M.; Ridwan, Ridwan; Hasanah, Siti (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2024)
This article offers a discussion on the law on medical cannabis utilization in the health sector from the perspective of the fatwas (official statement from an Islamic religious leader) of the Indonesian Islamic Scholar Assembly (MUI) and the Tarjih Council of Muhammadiyah (Muhammadiyah Organizational Ijtihad Institution). This paper aims to provide insight into the legalization of medical cannabis in Indonesia and review the policies of other countries that have legalized cannabis for medical purposes. There needs to be a firm statement of MUI and Islamic organizations such as Muhammadiyah on this issue. This paper employed the normative research method. It used the statute approach to profoundly analyze the available legal materials. The data were sourced from secondary legal materials. The data were collected by reading, studying, and understanding the materials related to the legal issue. The data were analyzed using the qualitative technique. Research results showed the findings that the fatwas of MUI and Tarjih Council of Muhammadiyah permit the usage of medical cannabis for treatment under emergency reasons and with strict supervision from doctors. It is crucial to have a fatwa in determining the legalization of medical cannabis, considering that Indonesia has the largest Muslim population in the world, and up to now, there has not been a firm legal policy that regulates the use of medical cannabis. The existence of a fatwa in determining the law benefits human beings both in the world and in the Hereafter. Apart from that, it brings tranquility in resolving the issue of the Muslim community. This paper brings novelty as it provides information on how other Muslim countries view the legalization of cannabis as well as the perspectives of MUI and the Tarjih Council of Muhammadiyah on this issue.